Benefits of inter-firm relationships: application to the case of a five sawmills and one paper mill supply chain. Issue 3 (2nd July 2016) - Lehoux, Nadia; LeBel, Luc; Elleuch, Momen
ABSTRACT: To access new markets and efficiently satisfy customer demand, many companies have decided to create collaborations with their suppliers, distributors, and even competitors. In this way, they can share the information needed to plan supply chain activities adequately while generating benefits that would not be achievable individually. In this project, we have studied the case of five sawmills that all shared the same important customer for their wood chip. That customer, a major paper mill, was facing significant difficulties and needed to benefit from more reliable, predictable and cost competitive wood flow from its suppliers. The main goal of the research was, therefore, to develop a collaboration scheme that would help these forest products companies to work together and to achieve in the long-term higher profitability. Results showed that sawmills could improve their profit by up to 44% by managing inventories for their main customer or jointly plan supply chain operations. Furthermore, based on game theory techniques such as Shapley value, we observed that greater collaboration may not be equally profitable for each supply chain member regarding their contribution. In our case study, the paper mill would need to share a portion of the benefits with its suppliers to ensure win–win collaboration.